Analisis Pengendalian Biaya Produksi dalam Meningkatkan Laba pada UMKM Soto Abas Trunojoyo - Tria Nurul Arofah; Elysa Puji Nur Rochmah; Dina Maulidia; Fifin Kurniawati; Hoirul Anam; Moh. Zeinor Ridho; Mochamad Reza Adiyanto (Universitas 45 Surabaya, 2025)
MSMEs have a very important role in the Indonesian economy, but often face challenges, especially in managing production costs efficiently. This research focuses on analyzing the management of production costs in Soto Abas Trunojoyo MSMEs with the aim of evaluating the extent to which cost control can increase business profits. The research method used was qualitative with a descriptive approach, where data regarding production costs, sales, and operational practices were obtained through direct interviews with business owners. The results revealed that production cost control, especially on raw materials, contributed greatly to operational efficiency and increased profits. The business managed to record a net profit of Rp17,875,000, which was largely achieved through effective cost management. This research emphasizes the importance of production cost management strategies in ensuring the sustainability of MSMEs. However, this study is limited to one business, so the results may not be representative of MSMEs in general. Future research is recommended to involve more types of MSMEs and use a combination of methods to deepen the analysis on cost management and business sustainability.